2015
DOI: 10.15740/has/arjss/6.1/1-8
|View full text |Cite
|
Sign up to set email alerts
|

A study on emotional intelligence of adolescents

Abstract: Technology and Sciences, ALLAHABAD (U.P.) INDIAThe present study was taken up to find out the emotional intelligence levels of adolescents and to find out the differences among them due to different sociocultural background. The sample size comprised of 325 adolescents (16-18 years) drawn from urban, rural and tribal areas of Jorhat district of Assam. It can be highlighted from the results that the level of emotional intelligence of most of the adolescents was far better in the dimension of interpersonal manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…It was because urban PUC students got greater emotional support from their family members to share and express their feelings at each ups and downs of their life without imposing strict rules and regulations. Results are on par with Saikia et al, (2015) who reported that adolescents of urban culture were more skilled in emotional intelligence than rural adolescents.…”
Section: Resultssupporting
confidence: 51%
“…It was because urban PUC students got greater emotional support from their family members to share and express their feelings at each ups and downs of their life without imposing strict rules and regulations. Results are on par with Saikia et al, (2015) who reported that adolescents of urban culture were more skilled in emotional intelligence than rural adolescents.…”
Section: Resultssupporting
confidence: 51%
“…Therefore, an individual who is emotionally intelligent has a high degree of importance, as its elements are essential requirements for progressing and achieving success in many aspects of life, whether at personal or academic levels. Generally, individuals with high emotional intelligence are healthier and more adaptive in their private and working lives, can establish strong social relationships and have strong leadership capabilities compared to individuals with low emotional intelligence (Abu Ghazal, 2015;Kelly & Moon, 1998;Saikia & Mathur, 2015).…”
Section: Body Image and Emotional Intelligencementioning
confidence: 99%